PENGARUH AUDIT TENURE, UKURAN KANTOR AKUNTAN PUBLIK, DIVERSIFIKASI GEOGRAFIS, DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan-Perusahaan Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2013) - Hasanuddin -; Andreas -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of audit tenure, audit firm size, geographic diversification and leverage towards earnings management in food and beverage companies. Audit tenure is measured by the amount of the year of work relationship between auditee and the last public accountant firm. Audit firm size is measured by dummy variabel. The Audit firm is divided into audit firms that affiliated with big four and non big four audit firms. Geographic diversification is measured by the number of firms geographic segments.And leverageratio is calculated by dividing total assets by total equity.The population of this study are the food and beverage companies that listed in Indonesia Stock Exchange (BEI) in 2011, 2012, and 2013. Purposive sampling is used for sampling method and multiple regression technique is used for the data analysis. The total number of samples for this study are 36 companies. The result of this study indicates that audit tenure don’t have significant influence in earnings management, audit firm size have negative significant influence in earnings management, geographic diversification have positif significant influence to earnings management. Meanwhile, leverage have positif significant influenceto earning managementKeywords: earnings management, audit tenure, audit firm size, geographic diversification, leverage